2016
DOI: 10.1001/jamaneurol.2016.0389
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for Pain in a Family With Inherited Erythromelalgia Guided by Genomic Analysis and Functional Profiling

Abstract: IMPORTANCE There is a need for more effective pharmacotherapy for chronic pain, including pain in inherited erythromelalgia (IEM) in which gain-of-function mutations of sodium channel Na V 1.7 make dorsal root ganglion (DRG) neurons hyperexcitable. OBJECTIVE To determine whether pain in IEM can be attenuated via pharmacotherapy guided by genomic analysis and functional profiling. DESIGN, SETTING, AND PARTICIPANTS Pain in 2 patients with IEM due to the Na V 1.7 S241T mutation, predicted by structural modeling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 33 publications
3
71
0
Order By: Relevance
“…These are undergoing clinical trials 2,91. Finally, advancement in electrophysiology, molecular modeling, thermodynamic analysis, and functional analyses profiling is improving our understanding of the molecular mechanisms underlying pain in EM 51. These studies are much needed to address the pain and significant comorbidity in patients with EM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are undergoing clinical trials 2,91. Finally, advancement in electrophysiology, molecular modeling, thermodynamic analysis, and functional analyses profiling is improving our understanding of the molecular mechanisms underlying pain in EM 51. These studies are much needed to address the pain and significant comorbidity in patients with EM.…”
Section: Resultsmentioning
confidence: 99%
“…Carbamazepine has not been found to have significant effects on pain in EM. However, there is some evidence suggesting that individuals who carry a specific mutation on the Nav1.7 sodium channel (V400M) may be more responsive to carbamezepine 4951. Oxcarbazepine has been used in inherited EM.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Patients with IEM start to exhibit symptoms as early as 1 year of age and as late as late-teens, and episodes of burning pain are triggered by mild warmth or exercise together with erythema and mild swelling in the hands and feet, with partial relief of symptoms by cooling affected extremities [45]. Despite the apparent uniformity of these symptoms, one recent study that looked in more details into the natural history of IEM in a cohort of 13 patients from four families demonstrated substantial variability in symptom presentation and triggers among members of the same family, including, for example, patients who reported that cooling evokes pain rather than relieves pain [82], while another study on two patients (parent/child) showed large variability in the severity of ongoing pain and in the number of nightly awakening due to pain [55]. The distinct patterns of affected body regions in IEM and PEPD, and the substantial variability of pain symptoms among members of the same family with the same mutation in IEM, suggest additional factors that regulate the severity of the symptoms and which parts of the body are affected.…”
Section: Nav17 In Human Pain Disordersmentioning
confidence: 99%
“…The lack of efficacy of sodium channel blockers in patients with Na v 1.7 IEM mutations is not well understood, albeit in one case it has been linked to a reduced affinity of the mutant channel, Asn395Lys, to sodium channel blockers that bind at the local anesthetic binding site [102]. However, there are case reports of effective treatment with mexiletine in a patient carrying the Val872Gly [27], and CBZ in patients carrying the mutations Val400Met [52] and Ser241Thr [55]. The efficacy of mexiletine in the patient carrying the Val872Gly mutation has been linked to a stronger use-dependent fall-off in the current [27].…”
Section: Nav17 As a Validated Target For Development Of Pain Therapementioning
confidence: 99%
“…Inhibiting VGSCs with small molecules reduces sensory neuron excitability [17,18,19]. Further, block of the channel by small molecules shows that Na v 1.7 contributes to the major TTX-sensitive Na + current in both small-diameter mouse and human DRG neurons [20,21,22]. In mice, the genetic deletion of VGSCs produces striking decreases in normal and pathological pain [23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%